Noninvasive Brain Stimulation and Personal Identity: Ethical Considerations - Iwry, Jonathan; Yaden, David B.; Newberg, Andrew B. (Frontiers in Human Neuroscience, 2017)
As noninvasive brain stimulation (NIBS) technology advances, these methods may become increasingly capable of influencing complex networks of mental functioning. We suggest that these might include cognitive and affective processes underlying personality and belief systems, which would raise important questions concerning personal identity and autonomy. We give particular attention to the relationship between personal identity and belief, emphasizing the importance of respecting users’ personal values. We posit that research participants and patients should be encouraged to take an active approach to considering the personal implications of altering their own cognition, particularly in cases of neurocognitive “enhancement.” We suggest that efforts to encourage careful consideration through the informed consent process would contribute usefully to studies and treatments that use NIBS.